2019
DOI: 10.1542/peds.2018-4064
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Palivizumab for Respiratory Syncytial Virus: A Systematic Review

Abstract: CONTEXT: Palivizumab prophylaxis is used as passive immunization for respiratory syncytial virus (RSV). However, because of its high cost, the value of this intervention is unclear. OBJECTIVE: To systematically review the cost-effectiveness of palivizumab prophylaxis compared with no prophylaxis in infants <24 months of age. DATA SOURCES: Medline, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 51 publications
3
66
0
1
Order By: Relevance
“…Although some experts believe that cost was an influencing factor for the policy change, the AAP stated that the similar risk of RSVH in > 29 wGA infants and term infants was the rationale for the change [ 23 , 55 ]. While the cost-effectiveness of palivizumab has been debated, many studies have shown that it is efficacious in the pediatric populations for which it is indicated [ 56 ]. Placebo-controlled randomized clinical studies have continually shown that palivizumab effectively reduces the risk of RSVH in 32–35 wGA infants.…”
Section: Changes In Rsv Ip Guidancementioning
confidence: 99%
“…Although some experts believe that cost was an influencing factor for the policy change, the AAP stated that the similar risk of RSVH in > 29 wGA infants and term infants was the rationale for the change [ 23 , 55 ]. While the cost-effectiveness of palivizumab has been debated, many studies have shown that it is efficacious in the pediatric populations for which it is indicated [ 56 ]. Placebo-controlled randomized clinical studies have continually shown that palivizumab effectively reduces the risk of RSVH in 32–35 wGA infants.…”
Section: Changes In Rsv Ip Guidancementioning
confidence: 99%
“…Palivizumab, a humanized monoclonal antibody used to prevent RSV infections, has shown evidence that it may significantly reduce acute and chronic morbidity following RSV infection in preterm infants (126,127). The use of palivizumab is generally restricted, however, due to the high financial cost of the treatment and uncertainty regarding cost-effectiveness (128,129).…”
Section: Early Life Virusesmentioning
confidence: 99%
“…There is existing evidence supporting the efficacy of monoclonal antibodies in providing passive protection in RSV. Palivizumab, a monoclonal antibody that targets the F‐protein, has a moderate effect in preventing RSV in at risk infants 12 . Its use has been restricted to high‐risk neonates in most jurisdictions by a combination of issues, including the cost, partial efficacy and the need for multiple doses throughout the season to maintain efficacy.…”
Section: Priming the Old And Protecting The Newmentioning
confidence: 99%